A comparison of energy absorbing capabilities of paper and steel structures subjected to progressive failure under free falling objects - Shah, Qasim Hussain; Abakrb, Yousif A. (Taylor's University, 2007)
An inverted paper cup of 0.26 mm thickness was subjected to deformation under a freely falling steel ball at a velocity of 2.77 m/sec. The deformed features of the paper cup were measured. The dynamic loading event was simulated using piecewise linear plasticity material model in LSDYNA. Deformed shape of the paper cup in finite element model matched closely with experimental results with ignorable small discrepancies. The paper cup was able to absorb all the kinetic energy of the falling steel ball for the above mentioned falling speed and the ball did not bounce out of the cavity generated by the impact. In LSDYNA a similar size steel cup was also subjected to a freely falling ball with same speed and the energy absorbed was compared to the energy absorbed by the paper cup. It was found that under similar conditions a paper cup would undergo a significant progressive failure and absorb all the energy of the falling object.